Studies on characterization of nano CaCO3 prepared by the in situ deposition technique and its application in PP-nano CaCO3 composites - Mishra, Satyendra; Sonawane, S. H.; Singh, R. P. (Journal of Polymer Science Part B: Polymer Physics, 2005)
The elegant approach of in situ deposition technique was used for the synthesis of nano CaCO3 the nanosize of particles was confirmed by the X-ray diffraction (XRD) technique. Differential scanning calorimetry (DSC) was used for determination of the enthalpy. The nano CaCO3 polypropylene (PP) composites were prepared by taking 2 and 10 wt % of different nanosizes (21-39 nm) of CaCO3. Conversion of the alpha phase to beta was observed in the case of 2 wt % of a 30-nm sized amount of CaCO3 in a PP composite. The decrement in DeltaH and percent. crystallinity, as well as the increment in melt temperature were recorded for 6 wt % nano CaCO3 with a decrease in nanosize from 39 to 21 nm. The increment in tensile strength with an increase in the amount of nano CaCO3 was observed, and the tower particle size shoved Greater improvement. The improvement in thermal and mechanical properties is because of the formation of a greater number of small spherulites uniformly present in the PP matrix. (C) 2004 Wiley Periodicals, Inc.
Keywords: Crystallization; DSC; mechanical and thermal properties; nano CaCO3; polypropylene; XRD

Synthesis, characterization, and performance evaluation of novel stabilized TDI-based polyurethane coatings under accelerated weathering - Kumar, A. P.; Reddy, K. R.; Rana, S.; Lonkar, Sunil P.; Raut, K. G.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2005)
Some toluene dilsocyanate (TDI)-based polyurethane resins (PURs) for coating applications were synthesized with castor oil and their performance was estimated under accelerated UV weathering with and without a novel UV absorber. Changes in physical properties, chemical structure, and color of the samples were monitored by mechanical property testing, FTIR spectroscopy, and colorimetry, respectively. A stable polyurethane coating was achieved at 0.5% concentration of additive in the host matrix. Mechanical properties were also retained as in the pristine PUR after mixing. Commercial Tinuvin P and benzotriazole-based novel UV absorbers were found to improve the photoresistance of the PUR coating, and the highest efficiency of the novel UV absorber against weathering was estimated at 0.5 wt% concentration.(c) 2005 Society of Plastics Engineers.

Synthesis, characterization, and performance evaluation of polymeric HALS in ethylene-propylene-diene terpolymer (EPDM) - Lonkar, Sunil P.; Rana, S.; Singh, R. P.; Lacoste, Jacques; Gardette, Jean Luc; Jestin, F.; Brocord, E. (Journal of Macromolecular Science, Part A: Pure and Applied Chemistry, 2005)
A polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the maleic anhydride graft ethylene-propylene-diene terpolymer (EPDM) was synthesized. This involves photoinduced grafting of maleic anhydride groups on unsaturated sites of EPDM, followed by incorporation of amino terminated HALS. The grafting and functionalization reactions were characterized by FTIR and C-13 NMR spectroscopy. The surface changes upon degradation are studied by SEM. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The HALS grafted EPDM showed significantly improved photostabilizing efficiency.
Keywords: EPDM; light induced grafting; Photostabilization; polymeric HALS

Stabilization of gamma-sterilized biomedical polyolefins by synergistic mixtures of oligomeric stabilizers - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Tevtia, Amit K.; Singh, R. P. (Polymer Degradation and Stability, 2006)
The stabilization of polyolefins against gamma-sterilization has been studied with single or binary additive system. The present attempt is to utilize synergistic mixtures of stabilizers which are approved for food contact applications. Ethylene-propylene (EP) copolymer has been melt-mixed with hindered amine stabilizers (HAS), phenolic antioxidants and organo-phosphites (hydroperoxide decomposer). Samples were sterilized with different doses of gamma-radiation. Stabilization was characterized in terms of changes in the functional groups (oxidation products), tensile properties, yellowing and surface morphology by FTIR spectroscopy, Instron, colorimetry (reflectance) and scanning electron microscopy (SEM), respectively. Results were discussed by comparing the stabilizing efficiency of mixtures with and without phenol system. Among phenol containing systems, where we mostly observe discoloration due to the oxidation of hindered phenol and the combination of secondary HAS, tertiary HAS, organo-phosphite and hindered phenol exhibited improved stabilization efficiency than single or binary additive systems. The mixture of secondary HAS and tertiary HAS, has shown antagonistic effect of stabilization whereas their combination with organo-phosphite has exhibited synergistic effect of stabilization even at higher doses of gamma-sterilization. The effects have been explained through the interaction between the stabilizers. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Antioxidants; discoloration; ethylene-propylene copolymer; gamma-sterilization; stabilization; tensile properties

Stabilization of gamma-sterilized biomedical polyolefins by synergistic mixtures of oligomeric stabilizers. part II. polypropylene matrix - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2007)
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Synthesis and characterization of hindered amine light stabilizers based on end functionalization of polypropylene - Reddy, K. Raghunatha; Kumar, Bijendra; Rana, Sravendra; Tevtia, Amit K.; Singh, R. P. (Journal of Applied Polymer Science, 2007)
A polymeric hindered amine light stabilizer (HALS), where HALS moiety was attached at the terminal end of the polypropylene chain via end-functionalized vinylidine PP through simple organic reactions, was synthesized. It comprises the synthesis of vinylidine-terminated polypropylene by using Cp2ZrCl2/MAO as catalyst system and epoxidation of vinylidene polypropylene. The final product was synthesized by carrying out the reaction between epoxy end functionalized polypropylene and 4-amino-2,2,6,6-tetrametyl piperidine. The final product was characterized by using H-1 NMR, C-13 NMR, and FT-IR spectra. Functionality was calculated by using vapor phase osmometry and H-1 NMR. The solubility and diffusion coefficient of the product were calculated and also its stabilization performance was checked. (c) 2007 Wiley Periodicals, Inc.
Keywords: end functionalization; functionalization of polymers; polymeric HALS; polypropylene; vinylidine and photostabilization

Studies on the feasibility of recycled polystyrene doped with NLO active meta-Nitroaniline for optoelectronics applications - Sureshkumar, M. S.; Goyal, R. K.; Negi, Y. S.; Pratheepkumar, A.; Reddy, K. Raghunatha; Singh, R. P.; Dadge, Jagdish W.; Aiyer, Rohini C. (Polymers for Advanced Technologies, 2011)
A Guest-Host system based on meta-Nitroaniline (m-NA) and recycled polystyrene (RPS) susceptible to generate nonlinear optically (NLO) active property such as second harmonic generation (SHG) has been prepared. Pure, sublimed, optical grade, crystalline m-NA is used as a guest and RPS from the disposable packaging waste as available utilized as the host polymer. In this paper we report the effect of NLO active m-NA on the bulk and optical properties of RPS. The purified m-NA was incorporated from 1-10 wt% in the RPS polymer matrix by conventional solution casting method. Thin, transparent, freestanding films obtained were characterized with optical microscope, scanning electron microscope (SEM), viscosity measurement, and UV-Visible (UV-Vis) spectroscopy for bulk properties evaluation and Nd:YAG laser studies for optoelectronics application such as SHG through frequency doubling. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: frequency doubling; guest-host NLO systems; meta-Nitroaniline; nonlinear optical activity; Polystyrene; second harmonic generation

Self photostabilizing UV-durable MWCNT/polymer nanocomposites - Lonkar, Sunil P.; Kushwaha, Omkar S.; Leuteritz, Andreas; Heinrich, Gert; Singh, R. P. (RSC Advances, 2012)
A potentially active hindered amine light stabilizer (HALS) was successfully anchored onto multiwalled carbon nanotubes (MWCNTs) and used as a light-stabilizing yet reinforcing multifunctional nanofiller to obtain UV-durable polymer nanocomposites. The influence of such light stabilizing MWCNTs on the photo-oxidation behaviour and structure-properties of polypropylene (PP) was studied. The composites were prepared by solution mixing of MWCNTs followed by melt compounding with polypropylene (PP). The resulting composite exhibits excellent UV-durability showing an almost 20 fold increase in the induction period of photo-oxidation. Moreover, the hydrophobic HALS was found to be compatibilizing enough to achieve homogeneous dispersion of exfoliated nanotubes into a polymer matrix. The rheological characterizations predict the formation of a percolated network structure. The obtained nanocomposites present markedly improved mechanical properties which underline the reinforcing ability of functionalized MWCNTs. Overall combination of HALS and MWCNTs offers an attractive route to combine multifunctionality into new hybrid UV-durable polymer nanocomposites. Such materials may possess great potential for outdoors high performance applications.

Synthesis and characterization of a new diol-functionalized s-triazine-based polymerizable hindered amine light stabilizer - Mehare, Rupali S.; Lonkar, Sunil P.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2012)
A new diol-functionalized triazine-based polymerizable hindered amine light stabilizer (HALS) was synthesized in two steps. First, selective synthesis of an s-triazine containing two HALS moieties as substituents was accomplished by using phase-transfer catalysis. This step required the establishment of optimum reaction conditions (type of two-phase system, best solvent, and catalyst). In the second step, the substituted triazine was treated with diethanolamine to introduce polymerizable diol functionality. The resulting product should act as a light stabilizer, since it contains two HALS moieties anchored to a thermally stable s-triazine unit. Moreover, incorporation of the diol into a polymeric material might be expected to impart prolonged stability in weathering environments. Characterization of the diol was accomplished by using Fourier transform infrared spectroscopy (FTIR), `H NMR, and mass spectrometry. J. VINYL ADDIT. TECHNOL., 18:204208, 2012. (c) 2012 Society of Plastics Engineers